G4CVE: um framework baseado em CSCW para o desenvolvimento de ambientes virtuais colaborativos - Miranda, Frederico Severo (Anais do Workshop sobre Aspectos da Interação Humano-Computador na Web Social (WAIHCWS), 2017)
The collaborative virtual environments are an important category of CSCW system (groupware) and has become increasingly popular for supporting group work and development of a wide variety of applications in different areas. Currently, there is not a model to build these virtual environments taking into account the approach of the CSCW/groupware. This article proposes to create a framework and test it on a prototype in development. As a result presents the framework Groupware for Collaborative Virtual Environments (G4CVE). This framework is still incipient, but can now be used to direct the development of collaborative virtual environments.